RESOLUTION OF THE INDEPENDENT EXPERT COUNCIL IN THE FIELD OF PREVENTIVE IMMUNIZATION ADDRESSING THE ISSUE OF IMMUNIZATION AGAINST TUBERCULOSIS - article Editorial (Union of pediatricians of Russia, 2021)
.